2021
DOI: 10.7861/clinmed.2020-1072
|View full text |Cite
|
Sign up to set email alerts
|

The Volunteers in Research programme: supporting COVID-19 research and improving medical training in parallel

Abstract: COVID-19 has had an unprecedented impact on society, global healthcare and daily life. The redeployment of research staff to patient-facing roles in the NHS left a depleted workforce to deliver critical urgent public health research (UPHR). We aimed to support UPHR studies and medical student training by developing and implementing a medical student Volunteers in Research programme. We further sought to gain insights about medical students' perceptions of this programme. We collected prospective data and condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Nine studies described the types of volunteering activities carried out by health professional students during the pandemic ( 7 , 8 , 22 , 25 , 27 , 39 , 46 48 ). The activities can be broadly divided into nine different categories, defined as hospital works (triage, admission wards, and emergency room) ( 7 , 25 , 27 , 46 ), call center and administration ( 7 , 27 , 39 , 46 ), epidemiological aspects (contact tracing, testing) ( 22 , 47 , 48 ), online or remote consultation (regarding COVID-19 or non-COVID-19 cases, using phone or internet) ( 46 49 ), laboratory-related works ( 47 ), food and/or PPE supply ( 27 , 39 ), mentoring juniors ( 39 ), public education (such as countering hoaxes) ( 48 ), and in research programs ( 8 ). Some students also reported participating in more than one type of volunteering activity ( 7 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nine studies described the types of volunteering activities carried out by health professional students during the pandemic ( 7 , 8 , 22 , 25 , 27 , 39 , 46 48 ). The activities can be broadly divided into nine different categories, defined as hospital works (triage, admission wards, and emergency room) ( 7 , 25 , 27 , 46 ), call center and administration ( 7 , 27 , 39 , 46 ), epidemiological aspects (contact tracing, testing) ( 22 , 47 , 48 ), online or remote consultation (regarding COVID-19 or non-COVID-19 cases, using phone or internet) ( 46 49 ), laboratory-related works ( 47 ), food and/or PPE supply ( 27 , 39 ), mentoring juniors ( 39 ), public education (such as countering hoaxes) ( 48 ), and in research programs ( 8 ). Some students also reported participating in more than one type of volunteering activity ( 7 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…Fourteen studies revealed the benefits of participating as a volunteer during the current pandemic from the health professional students’ perspectives ( 7 , 8 , 16 , 17 , 22 , 24 , 27 , 28 , 46 , 47 , 50 53 ). The most frequently mentioned advantage was to learn and practice, especially to give real aid and explore evidence-based medicine ( 8 , 16 , 17 , 22 , 24 , 28 , 47 , 53 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations